2022
DOI: 10.3390/polym14183743
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Resistant, Self-Extinguishing Thermoplastic Composites Enabled by Tannin-Based Carbonaceous Particulate

Abstract: Flame-resistant materials are key components in buildings and several other engineering applications. In this study, flame retardancy and thermal stability were conferred to a highly flammable technical thermoplastic—polypropylene (PP)—upon compositing with a carbonaceous tannin-based particulate (CTP). Herein, we report on a straightforward, facile, and green approach to prepare self-extinguishing thermoplastic composites by thermoblending highly recalcitrant particulate. The thermal stability and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…A narrow absorption at 1440 cm À1 is attributed to O H bending in the carboxylic acid group. 2,39 In the peroxide-cured sample of EPDM (Figure 5C), similar FTIR peaks are observed at 2910 and 2850 cm À1 , corresponding to C H stretching from the CH₂ groups. The peak at 1733 cm À1 is due to the C O stretching of a carboxylic acid.…”
Section: Fourier Transform Infrared Spectroscopy Analysismentioning
confidence: 68%
See 1 more Smart Citation
“…A narrow absorption at 1440 cm À1 is attributed to O H bending in the carboxylic acid group. 2,39 In the peroxide-cured sample of EPDM (Figure 5C), similar FTIR peaks are observed at 2910 and 2850 cm À1 , corresponding to C H stretching from the CH₂ groups. The peak at 1733 cm À1 is due to the C O stretching of a carboxylic acid.…”
Section: Fourier Transform Infrared Spectroscopy Analysismentioning
confidence: 68%
“…The peak at 1540 cm −1 is due to the CS bonds from TMTD and DPTT. A narrow absorption at 1440 cm −1 is attributed to OH bending in the carboxylic acid group 2,39 …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have proved the ability of these foams to match synthetic foams based on the positive characteristics of thermal insulation, low density, and reduced cost [24][25][26]. Unlike PU foams, the main advantage of TA foams is their exceptional fire-resistance characteristics, together with their low emission of smoke and harmful gases [27][28][29], which further reinforces the great potential of these foams in the replacement of conventional petrochemical foams in the most diverse applications, including sandwich panels. Li et al, for example, produced foams derived from tannin-furanic resins with distinct cellular/nonporous structures and registered an excellent thermal conductivity of 0.0239 W/m•K [30], while Li et al found that increasing the larch tannin content (LT) in tannin rigid foams contributed to increases in the thermal conductivity from 0.03252 W/m•K (when the LT was 10%) up to 0.04345 W/m•K (when LT reached 30%) [31].…”
Section: Introductionmentioning
confidence: 88%
“…This improvement in the thermal stability of tannincontaining polymers has been widely reported in various types of materials, which propose the addition of tannins as an environmentally friendly and economical alternative for the formation of intumescent flame retardant polymers. 37,38 However, there are some challenges that still need to be addressed such as the high percentages of tannins required and the effect that these high concentrations have on the mechanical properties of the materials. 39 Therefore, several studies related to the development of this type of materials are still needed.…”
Section: Assessing the Properties Of The Tannin Polymer Obtained From...mentioning
confidence: 99%